A Generalized Dynamic Programming Modelling Approach for Integrated Reservoir Operation - Rani, Deepti (2020)
In water resource systems, the demands at each reservoir are generally known. However, in the integrated operation of a system involving inter-basin water transfers, the import/export of water among various reservoirs also plays an important role in the sustainable and optimal management of available water. Generally, a trial and error approach is adopted to simulate a system for integrated operation. Prior information on water resettlements among reservoirs would be helpful for facilitating the integrated management of these systems. In the present study, a generalized inventory-based dynamic programming model is developed to evaluate the water transfers between reservoirs in the Alqueva subsystem. The model offers guidelines on water transfers among reservoirs and estimates the overall amount of water to be pumped from the Alqueva reservoir to subsidize the shortfalls in the Alqueva subsystem. The proposed methodology may be adapted to other complex systems to promote integrated operations, and the model may be useful for design and operational purposes.